Upaya Jaksa Selaku Eksekutor dalam Pengembalian Kerugian Keuangan Negara Hasil Tindak Pidana Korupsi: (Studi Kasus di Kejaksaan Negeri Kota Kupang) - Louis Hangri Aldiano Dasilva; Rudepel Petrus Leo; Darius Antonius Kian (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2023)
The purpose of this research is to analyze the efforts of prosecutors as executors in recovering state financial losses resulting from corruption crimes. This research is an empirical legal research conducted at the Kupang City State Attorney's Office. The data collection technique uses observation, interview, and literature/document study techniques. The data used are primary and secondary data. This research was conducted in Kupang City. The results of data processing were analyzed descriptively qualitatively using the inductive method. Based on the results of research and discussion, it can be seen: (1) The efforts of the prosecutor as the executor at the Kupang City District Attorney's Office in recovering state financial losses due to corruption are four, namely, tracking, blocking, confiscation, seizure. (2) obstacles faced by prosecutors as executors in recovering state financial losses.